The Effect Of Isotonic Solution Immersion On Tooth Enamel Hardness After Topical Application Of CPP-ACPF And fTCP - Sri Wahyuni; Rini Bikarindrasari; Mutiara Nur Fauziah (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Introduction: The addition of topical CPP-ACPF and fTCP on tooth enamel can improve enamel hardness due to remineralization process. Demineralization can occur during acid environment in the oral cavity and enamel hardness can decrease. Objective: To determine the effect of isotonic solution immersion and compare tooth enamel hardness after CPP-ACPF and fTCP application. Methods: Thirty six crowns of maxillary first premolars were divided into three groups, each consisted of 12 tooth crowns. The baseline hardness of each sample (pre-test) was tested using Vicker’s Hardness Tester Digital. Afterwards, CPP-ACPF was applied to group A, fTCP was applied to group B, and artificial saliva to group C (control) for 24 hours, then the hardness was re-assessed (post-test 1). Immersion in isotonic solution was conducted for 24 hours to simulate demineralization process, then enamel hardness was re- assessed (post-test 2). Results: Paired t-test on post-test 1 revealed that all groups showed significant increase and post-test 2 showed significant enamel hardness decrease. The results of one-way ANOVA on pre-test showed that there was no significant difference, while post test 1 and post-test 2 revealed significant difference. Post-Hoc Bonferroni test showed that there was no statistically significant difference of enamel hardness between groups. Conclusion: There was an effect of isotonic solution immersion on tooth enamel hardness that were given topical CPP-ACPF and fTCP.